Effect of Sling Exercise Therapy on Adolescent Patients with Idiopathic Non-double-curved Scoliosis - Wudong SUN; Qian CAI; Jianye GUO; Xiaorui SHANG; Xianghu ZHAO; Liang XU; Ming MA (康复学报)
Objective:To observe the effect of sling exercise therapy on adolescent patients with idiopathic non-double-curved scoliosis.Methods:A total of 42 adolescent patients with idiopathic non-double-curved scoliosis who were treated in the department of rehabilitation medicine of Zhongda Hospital Southeast University from June to December 2019, which were randomly divided into the control group and the observation group according to the random number table method, with 21 cases in each group. The both groups were given conventional rehabilitation therapy, which including muscle and fascia relaxation in the concave spine(five minutes a time), respiratory therapy(six times per group, three groups a day, rest for 40 second between two groups), traction therapy(30 minutes a time). The control group was given mat training on the basis of conventional rehabilitation therapy, including double bridge, tummy roll, left or right plank movement, each movement training 8-10 times, continous training 4-6 groups, rest for 40-60 s between two groups. The observation group was given sling exercise therapy on the basis of conventional rehabilitation therapy, which including neutral position control training in supine position, lateral position and prone position(record the training time and terminate the exercise if patients experience pain or fatigue, each movement training 8-10 times, continous training 4-6 groups, rest for 40-60 s between two groups). The above training was conducted once every other day, three times a week, continous training for six months. Before treatment and after treatment for six months, Cobb angle was used to evaluate the severity of scoliosis; clavicular angle(CA)was used to evaluate the degree of shoulder imbalance; pelvic obliquity(PO)was used to evaluate the degree of pelvic imbalance; scoliosis research association-22 item questionnaire(SRS-22)was used to evaluate the patients'self-image satisfaction.Results:Before treatment, there were no significant differences in Cobb angle, CA, PO and SRS-22 scores between the two groups(P>0.05).Compared with before treatment, Cobb angle, CA and PO in both groups were significantly decreased, and SRS-22 score was significantly increased, with statistical significance(P<0.05).Compared with the control group, Cobb Angle, CA, PO in the observation group were lower, and SRS-22 score in the observation group was higher, with statistical significance(P<0.05).Conclusion:The sling exercise therapy can effectively improve AIS patients'scoliosis, shoulder imbalance, pelvic imbalance and self-image satisfaction, which is worthy of clinical promotion.